The Role of Digital Bureaucracy in Public Administration Transformation in the Era of Digital Government - Sunarso, Budi (ADMAN: Journal of Contemporary Administration and Management, 2025)
The transformation of public administration in the era of digital government requires bureaucracy to adapt through the systematic use of information and communication technology. The concept of digital bureaucracy emerges as a strategic approach to enhance efficiency, transparency, and the quality of public services. This study aims to analyze the role of digital bureaucracy in the transformation of public administration in the digital government era. The research method employed is a literature review with a qualitative and descriptive analysis approach. Data were obtained from scientific articles and credible sources published between 1990 and 2025 via Google Scholar and official institutional websites. Out of 50 identified articles, 31 were selected through a rigorous selection process based on relevance and academic quality. The findings indicate that digital bureaucracy plays a significant role in improving bureaucratic efficiency, public service integration, as well as governmental transparency and accountability. Case studies from various countries, such as Estonia, South Korea, Singapore, Indonesia, and India, show that the success of digital bureaucracy implementation is highly influenced by institutional readiness, human resource capacity, system integration, and sustainable policies. This study emphasizes that digital bureaucracy represents a comprehensive and contextual process of institutional transformation.